Social and economic differentials among household of urban migrants evidence from Kalutara District, Sri Lanka - Kanthi, Manel; Perera, Sunethra; Punpuing, Sureeporn (My University, 2017)
Attached

Migration to urban areas is a common phenomenon in Sri Lanka since more than three decades. Urban population is gradually increased mainly due to various reasons: socio-economic issues, natural disasters, political and ethnic issues, cultural requirements and improvement in transportation and communication, and migration to urban areas from rural and urban areas. As a result of the migration towards urban areas, socio-economic differences between formal and informal sector households have increased. Therefore, the aim of the study is to explore and estimate the socio-economic differences of urban migrants who are engaged in the formal and informal sector economic activities at the destination. Data was obtained quantitatively from a sample survey by using a face-to-face interview technique, covering 400 migrant households from three urban areas in Kalutara District and qualitative information was gathered using in-depth interview method. The factors related to social and economic differentials of migrant households were analysed by employing descriptive, bivariate and multivariate analyses. Findings of this study revealed that more than half of migrants belong to the reproductive age group. Three fourths of the household heads among migrants are below secondary level education and parents’ aspiration towards the children’s education is quite low, especially in the informal sector. Most of the urban migrants’ employments are at risk because more than two thirds of migrant household heads are engaged in informal economic activities and more than half of households have no economic security of their urban life. According to the bivariate comparison, formal sector employed households differ significantly from informal sector employed households in terms of respondent’s age, resident years at destination, monthly household income, monthly household expenses and Household Assets Index. Furthermore, these differences are enhanced by the multivariate discriminant analysis. Moreover, the qualitative findings discovered that several community and environmental factors such as lack of sanitary facilities and low educational attainment, less awareness and encouragement of employment opportunities have resulted in increasing the negative economic influences within these urban communities. It is suggested that the future employment programs and awareness programs should directly focus on empowering, especially, informal employees and new policies should be introduced to reduce the migration towards urban areas and its negative influences on the destination community.
Keywords: Urban migrants, household differentials, formal & informal households, urban community